Skeletal-related events in advanced lung adenocarcinoma patients evaluated EGFR mutations - Nagata, Misato; Kudoh, Shinzoh; Mitsuoka, Shigeki; Suzumura, Tomohiro; Umekawa, Kanako; Tanaka, Hidenori; Matsuura, Kuniomi; Kimura, Tatsuo; Yoshimura, Naruo; Hirata, Kazuto (Osaka City medical journal, 2013)
The rate of lung cancer metastasis to the bone is high and skeletal-related events (SREs) decrease the quality of life in many patients. Recently, it was found that a subgroup of patients with non-small cell lung cancer (NSCLC) have specific mutations in the EGFR (epidermal growth factor receptor) gene. We assessed the SREs in advanced lung adenocarcinoma patients that evaluated EGFR mutations in whom bone metastasis was present. We retrospectively investigated the clinical records of 377 patients with advanced NSCLC. Patients were evaluated for the presence of EGFR mutations, bone metastases, the incidence of SREs, and treatment history before the first SRE. A total of 78 patients who were evaluated for EGFR mutations had bone metastasis from lung adenocarcinoma. The most frequent site of bone metastasis was the spine (36.2%). SREs occurred in 37 patients (47.4%), the most common of which was bone radiotherapy (41.0%). Significant differences were not observed in the sites of bone metastases or the patterns of SREs between patients with and without EGFR mutations. The median time from bone metastasis to the first SRE was 5.8 months in all of the subjects, history of EGFR-tyrosine kinase inhibitor (TKI) treatment was significantly associated with longer median time to first SRE (14.2 months vs 1.3 months, p < 0.0001), and the median time to first SRE of patients with PS 0-1 was longer (8.5 months vs 0.9 months, p = 0.0023). We found that SRE patterns have no difference between EGFR mutation positive and negative, and that the time from bone metastasis to the first SRE was longer in advanced lung adenocarcinoma patients with good PS and history of EGFR-TKI treatment.